Street Stops and Police Legitimacy: Teachable Moments in Young Urban Men’s Legal Socialization - Fagan, Jeffrey (2013)
An examination of the influence of street stops on the legal socialization of young men showed an association between the number of police stops and a diminished sense of police legitimacy. This association however is not only a consequence of the number of street or car stops they experience or of the degree of police intrusion that occurs during those stops. Rather, the estimated impact of involuntary contact with the police is mediated by evaluations of the fairness of police actions and judgments about whether the police are acting lawfully. Whether the police are viewed as exercising their authority fairly and lawfully directly shapes respondent’s decision acceptance and the impact of stops on respondent’s general judgments about police legitimacy. Fairness and lawfulness judgments, in turn, are influenced by the number of stops or the degree of police intrusion during those stops. Similarly, judgments of justice and lawfulness mediate the estimated influence of judgments of the general character of police behavior in the community on general perceptions of police legitimacy. These results suggest that the widespread use of street stops undermines legitimacy. Lowered legitimacy has an influence on both law abidingness and the willingness to cooperate with legal authorities. However, the findings also show that it is not only police streets or police conduct during such stops that matters per se, but more importantly public perceptions of police injustice/illegality during those stops. The results suggest that police legitimacy is shaped by how fairly/legally the police are viewed as exercising their authority